Comparative analysis of students’ emotional and motivational profiles in mathematics in grades 1–6 - Hanin, Vanessa; Gay, Philippe (Frontiers in Education, 2023)
Mathematics continues to be a real stumbling block for many low-performing students. Research over the past decades has highlighted the joint and determining effects of emotions and motivation on learning and performance in mathematics and has shown an increase in negative emotions over the course of schooling. Inter-individual emotional differences and increasing classroom heterogeneity necessitate a person-centered approach that focuses on particular combinations of variables as they exist within groups of individuals. The purpose of this cross-sectional research is twofold: (1) to identify the emotional profiles of 1505 elementary school students (ages 6-12) in mathematics, and (2) to document, on the basis of expectancy-value theory, how these profiles differ in terms of beliefs about competence, perceived value, and performance. The results highlighted two profiles over the six years: positive and negative. Three other profiles were observed repeatedly throughout schooling: the anxious, the self-esteem focused, and the emotionally disengaged. Three pivotal years emerged from the analyses: the first year (transition to a more formal type of teaching), the third year (enculturation in normative evaluation practices and social comparison) and the final year (centering of learning around the external certification test). In terms of the dependent variables, the tendency of young children to overestimate their competences attenuates their negative emotions and the undesirable effects of these in terms of learning. Anxious and full-negative profiles performed the poorest and placed less value on mathematical learning. These findings indicate that interventions addressing the specific needs of each age and profile are needed.